TERAPI FAVIPIRAVIR PADA SUBYEK COVID-19 DERAJAT SEDANG TANPA GANGGUAN LIVER DI RS PUSAT INFEKSI PROF DR SULIANTI SAROSO - Hastutik Cairn Brisbane; Abdul Rahem; Anita Purnamayanti; Rosamarlina Rosamarlina; Memy Aviatin; Adria Rusli (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
The outbreak of the corona virus which first contracted in December 2019 in Wuhan, China; Currently it has been designated by the World Health Organization (WHO) as a pandemic and is known as Corona Virus Infection Disease 2019 (Covid-19). This study aimed to describe the profile of favipiravir therapy in moderate COVID-19 inpatients without liver impairment at Prof. dr. Sulianti Saroso Infection Center Hospital. The design of this study was an observational study conducted retrospectively. All the patients in this research were received favipiravir loading dose of 1600 mg bid on the first day, and 600 mg bid starting on the day-2 of therapy. The results of the research were 81 moderate Covid-19 inpatients without history or recent liver impairment who were hospitalized in the period October 2020 - July 2021 dominating by female gender (56%). Mode of hospital admission were self-referral to Prof. dr. Sulianti Saroso Infection Center Hospital (83%), primary care (Puskesmas) referral (12%), and other hospital referral (5%). There were no comorbidity in 74,1% of the subjects. Among 25,9% subjects with comorbidity, most of the patients suffered from hypertension (29%); hypertension, and cardiovascular disease (17%). diabetes (12%); diabetes and hypertension (12%); Asthma (12). None of the subjects experienced increased in liver transaminases (ALT, AST), nor ALP and total bilirubin. Eighty-one patients were either cured (12%) with negative PCR test results or improved (88%) at the end of the therapy.